The Effect of Feet Reflection Massage on Blood Pressure in Hypertension Patients at Community Health Centers II Petang - Ni Kadek Yuni Lestari, Yuni; Ni Luh Putu Thrisna Dewi; Ni Made Era Mahayani (Nursing and Health Sciences Journal (NHSJ), 2023)
Complications of hypertension cause various health problems such as kidney damage, heart attack, stroke, glaucoma, erectile dysfunction, dementia and alzheimer's. One of the non-pharmacological treatments to avoid the long-term effects of hypertension is foot reflexology therapy. Foot reflexology therapy is a therapy that suppresses the zones and nerve points on the right and left soles of the feet. This study aims to determine the effect of foot reflexology on blood pressure in patients with hypertension. This type of research is a Quasi Experiment with a Non-Equivalent Control Group Design. The population in this study were all 102 people with hypertension in Pelaga village. The sample selection used was purposive sampling with a total of 36 people. Foot reflexology intervention is given 3 times a week for 20 minutes. The average difference in blood pressure before and after the foot reflexology intervention in the treatment group was 10.39 mmHg and the average difference in the control group was 0.94 mmHg. The results of the analysis used was Mann-Whitney analysis that is p-value of 0.000 (p <0.05), so it can be concluded that there is an effect of foot reflexology on blood pressure in hypertension sufferers in Community Health Center II Petang. Foot reflexology can be used as an alternative to non-pharmacological treatment programs for patients to prevent further complications from uncontrolled hypertension.